2021
DOI: 10.1093/humrep/deab070
|View full text |Cite
|
Sign up to set email alerts
|

The influence of frozen-thawed and fresh embryo transfer on utero-placental (vascular) development: the Rotterdam Periconception cohort

Abstract: STUDY QUESTION Does frozen-thawed or fresh embryo transfer (ET) influence utero-placental (vascular) development, when studied using three-dimensional (3D) ultrasound and virtual reality imaging techniques? SUMMARY ANSWER In the first trimester, placental developmental parameters, that is, placental volume (PV) and utero-placental vascular volume (uPVV), were comparable between pregnancies resulting from frozen-thawed ET, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
4
3
0
Order By: Relevance
“…Furthermore, conception by IVF was found to be associated with significantly decreased third trimester UtA-PIs. Since the vast majority of cases from our current series are from frozen-thawed embryo transfers, this is in agreement with previous major evidence from our group [20,21], recently confirmed by other authors [59].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, conception by IVF was found to be associated with significantly decreased third trimester UtA-PIs. Since the vast majority of cases from our current series are from frozen-thawed embryo transfers, this is in agreement with previous major evidence from our group [20,21], recently confirmed by other authors [59].…”
Section: Discussionsupporting
confidence: 93%
“…The PSV is utilised as a quantitative indicator of the likelihood of oocyte formation. The findings of our analysis support the results of previous studies conducted by Mayer et al [11] and van Duijn et al [9], which showed a favourable correlation between PSV levels surpassing 10 cm/s and increased rates of ovulation and conception. This suggests that PSV has the capacity to function as a valuable tool for predicting the outcome of a treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Choux et al showed that PI was significantly higher in the fresh embryo transfer group (1.86 ± 0.64) than in the naturally conceived (1.52 ± 0.59; p = 0.001) and Pi was lower in the eFET group compared to the fresh embryo transfer group ( p = 0.001) [ 3 ]. These results were confirmed by two other studies that observed lower UtA-PI values for the eFET group compared with the fresh-blastocyst-transfer group [ 54 , 55 ].…”
Section: Non-invasive Parameters In the First Trimester Of Placental ...supporting
confidence: 86%